Comunicação científica: agregação, compartilhamento e reuso de elementos informacionais - Araya, Elizabeth Roxana Mass [UNESP] (2014)
The press with a movable type system invented by Gutenberg was, for more than three centuries, the technology which made the scientific journal the main scientific communication medium for disseminating results from researches developed by the scientific community. Currently, Information and Communication Technologies (ICT), besides promoting the continuity of the scientific journal as a scientific communication medium, also allow the scientific knowledge, which is disseminated by the scientific journal, to be broadened. However, the scientific community has had to create means of putting this into effect. Therefore, the Free Access movement to scientific literature and the Creative Commons Licenses – alternatives for the intellectual property legislation – have contributed to make the access to this knowledge unrestricted. ICT have also made possible for information elements generated in processes, which are inherent to researches, and unfeasible in paper, to be shared in the cyberspace, and even to become new scientific communication unities. In the realm of science, however, it is not enough to just generate and make a larger number of information elements available. In order to confer them scientific value, they must be formally communicated in scientific journals and in textual format represented by the scientific paper as stipulated. Information elements that are not linked to the research process which has generated them lose a great deal of their informational value. In this sense, this descriptive study, characterized as a direct observational non-participative qualitative research, which explores the scientific communication based on the technological development, has concluded that ICTs not only allow the scientific communication to be broadened in terms of time, space and access, but they also allow aggregating, sharing and reusing these information elements by placing them in the established scientific communication ...